Transition‐Metal‐Based Electrocatalysts as Cocatalysts for Photoelectrochemical Water Splitting: A Mini Review - Li, Deng; Shi, Jingying; Li, Can (Small (Weinheim an der Bergstrasse, Germany), 2018)
Converting solar energy into hydrogen via photoelectrochemical (PEC) water splitting is one of the most promising approaches for a sustainable energy supply. Highly active, cost‐effective, and robust photoelectrodes are undoubtedly crucial for the PEC technology. To achieve this goal, transition‐metal‐based electrocatalysts have been widely used as cocatalysts to improve the performance of PEC cells for water splitting. Herein, this Review summarizes the recent progresses of the design, synthesis, and application of transition‐metal‐based electrocatalysts as cocatalysts for PEC water splitting. Mo, Ni, Co‐based electrocatalysts for the hydrogen evolution reaction (HER) and Co, Ni, Fe‐based electrocatalysts for the oxygen evolution reaction (OER) are emphasized as cocatalysts for efficient PEC HER and OER, respectively. Particularly, some most efficient and robust photoelectrode systems with record photocurrent density or durability for the half reactions of HER and OER are highlighted and discussed. In addition, the self‐biased PEC devices with high solar‐to‐hydrogen efficiency based on earth‐abundant materials are also addressed. Finally, this Review is concluded with a summary and remarks on some challenges and opportunities for the further development of transition‐metal‐based electrocatalysts as cocatalysts for PEC water splitting. Photoelectrochemical water splitting for hydrogen production is regarded as a promising way to harvest and store the intermittent solar energy. Highly efficient photoelectrodes require integrating of electrocatalysts onto the light absorbers. In this Review, the recent applications of transition‐metal‐based hydrogen evolution reaction and oxygen evolution reaction electrocatalysts as cocatalyst to be incorporated into photoelectrochemical systems for solar water splitting are summarized.